BIMBINGAN LITERASI FIKIH KELUARGA BAGI CALON PENGANTIN DALAM PEMBENTUKAN KELUARGA SAKINAH DI DKI JAKARTA - Bariyah, Oneng Nurul; Alfarisi, Usman (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
The high divorce rate in Indonesia is a very concerning social problem because the family is the main foundation of society. It became one of the motives for research on the Family fiqh literacy model for prospective brides in DKI Jakarta. This study aims to describe the model of guidance for prospective brides in increasing the understanding of prospective pengnatin about family fiqh literacy in DKI Jakarta. The research method is qualitative with descriptive analysis. Data collection is done by observation, interview, documentation study and literature study. The results showed that the family fiqh literacy guidance model carried out in Jakarta has two models, namely the Partnership Model and the Independent model. The partnership model is a cooperation activity of the KUA and BP4 where the material and facilitators are based on the technical guidelines of Bimas Islam and guided by certified facilitators as marriage guidance facilitators. In the first model, the guidance uses several methods such as the case method, lectures and questions and answers. The second model is an independent model in which the head of the KUA and its staff provide counselling guidance to prospective brides using the lecture method. The second model is a form of initiative on the part of the KUA so that prospective brides who do not get marriage education material from the government still have knowledge even though it is limited.